Extrinsic and intrinsic control of striatal cholinergic interneuron activity - Desh Deepak Ratna; Tanner Chase Francis (Frontiers in Molecular Neuroscience)
The striatum is an integrated component of the basal ganglia responsible for associative learning and response. Besides the presence of the most abundant γ-aminobutyric acid (GABA-ergic) medium spiny neurons (MSNs), the striatum also contains distributed populations of cholinergic interneurons (ChIs), which bidirectionally communicate with many of these neuronal subtypes. Despite their sparse distribution, ChIs provide the largest source of acetylcholine (ACh) to striatal cells, have a prominent level of arborization and activity, and are potent modulators of striatal output and play prominent roles in plasticity underlying associative learning and reinforcement. Deviations from this tonic activity, including phasic bursts or pauses caused by region-selective excitatory input, neuromodulator, or neuropeptide release can exert strong influences on intrinsic activity and synaptic plasticity via diverse receptor signaling. Recent studies and new tools have allowed improved identification of factors driving or suppressing cholinergic activity, including peptides. This review aims to outline our current understanding of factors that control tonic and phasic ChI activity, specifically focusing on how neuromodulators and neuropeptides interact to facilitate or suppress phasic ChI responses underlying learning and plasticity.